Four-Tier Diagnostic Test to Assess Student Misconceptions About the Human Circulatory System - Tesa Ihutmarito Ambarita; Lilit Rusyati (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
Misconceptions persist and hinder the achievement of learning goals. The purpose of this study is to identify and explain issues that arise when students attempt to comprehend the circulatory system concept. A multiple-choice questionnaire based on the Four-Tier Diagnostic Test question model that has been validated serves as the instrument. Students have the validity tested by distributing it and using the R-Table is greater than the R-Count. Three experts delivered an average value of 0.73, which was then used in Aiken's Test. The study reveals that the majority of students (36.2%) have a low level of understanding of the human circulatory system. This is due to students' tendency to memorize scientific terms and difficulty understanding the system. The percentage of students in the FP and FN categories is relatively low, with 14.9% and 10.2% respectively. This suggests that students' understanding of the concept is similar to the percentage of M (27.6%). SK, which comprises 11.1% of overall student responses, is the lowest compared to LK, M, and collaboration of FP and FN categories. This low SK percentage can be attributed to limited hands-on activities, inadequate teaching methods, and insufficient emphasis on the circulatory system's importance in overall health.